Lung Cancer Strategies for Diagnosis and Treatment - Fabiola Costa Torres, Alba (IntechOpen, 2018)
Among the deadliest type of cancers, lung cancer faces several challenges in diagnosis and treatment: late diagnosis and misdiagnosis, inadequate tumor sampling, and resistance development to current therapies, among others. Together with advances in the understanding of molecular features, factors, and mechanisms involved in initiation and tumor progression, important improvements have occurred in diagnostics and therapeutics in the shape of advances in molecular genotyping, procedures for sampling, new potential, and less invasive sources of samples for the diagnosis and development of new targeted therapies. The aim of this book is to provide an exciting read on strategies in the diagnosis and therapy of lung cancer.